(untitled) (La U Investiga, 2018)
Gastric cancer is the second cause of cancer mortality worldwide, it is one of the most frequent problems in public health in any modern society, due to many social, family and individual factors. Currently, three countries account for 60% of the total gastric cancers in the world, which correspond to Japan, China and Korea. In Ecuador, while talking about Zone 3, studies conducted during 2004 and 2015 indicate a high occurrence in the provinces of Bolívar, Los Ríos, Chimborazo, Tungurahua and Cotopaxi. With a type of prospective retrospective diagnosis in this investigation, the values of the tumor marker CA 19.9 before and after chemotherapy were determined in patients with gastric cancer, of the Dr. Julio Enrique Paredes Solca Tungurahua Hospital, the importance of the use of said tumor marker in the follow-up of patients with gastric cancer to analyze the evolution was essential. We worked with 50 patients suffering from gastric cancer established by exclusion criteria such as: patients who have completed or have withdrawn chemotherapy treatment, as well as those who have not been determined the tumor marker CA 19.9. Of these, 60% of the patients were male, the average age was 60 to 80 years. 68% of the patients presented gastric adenocarcinoma in stage IIIB. The majority of patients were receiving neoabyubant chemotherapy. At the end of the investigation, a decrease of the marker was observed in 92%, and a rise in the remaining 8% after the treatment, with the cases that presented progression of the disease.